Green Accounting for Eco Friendly Bamboo Products in the "Virageawie" Community Group of Disabled People in Cimareme – West Bandung Regency - Andhika Mochamad Siddiq; Deni Hamdani; Rizki Surya Tawaqal (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2026)
By incorporating green accounting into the manufacturing of eco-friendly bamboo-based goods, this community service initiative aims to increase the Difabel Virageawie Community's economic independence. The initiative was started in response to a number of issues that the community was facing, such as low use of digital marketing platforms, uneven product quality, lack of standardized production processes, and low financial literacy. The activity's primary goals were to improve participants' digital marketing abilities, increase their proficiency in financial records based on environmental principles, and create a more organized and sustainable bamboo production process. The techniques used included needs analysis, interactive training, hands-on workshops, mentoring, and the creation of digital tools that are accessible to people with disabilities. The creation of Standard Operating Procedures (SOPs), branding, digital marketing, and Green Accounting ideas were all covered in the course. The findings showed notable advancements: members' average income rose by 35%, their comprehension of financial reporting climbed by 63%, and their proficiency with digital marketing increased by 72%. In order to facilitate the advertising of digital products, an accessible website was also effectively created. All things considered, this initiative effectively improved the community's financial capacity, entrepreneurial ability, and sustainable economic practices. Keywords: Bamboo products; Digital Marketing; Disability Empowerment; Environmental sustainability; Green Accounting